(untitled) (Comprehensive Journal of Science, 2025)
Wheat and barley are among the most important strategic crops in Libya, as the country is considered one of the world’s largest importers due to the inability of local production to meet the growing domestic needs. The importance of wheat and barley lies in their status as essential cereal crops in global food consumption and their wide use in various industries such as animal feed and bread production. Moreover, their varieties play a fundamental role in shaping the policies of some countries that exert pressure on non-producing nations. Declines in production and productivity contribute to widening the food gap and creating an imbalance between supply and demand. This study aims to examine the actual status of total production, productivity, and cultivated areas of wheat and barley in the Tarhuna region during the period (2010–2025). The study relied on published data from the Human Resources Department of the Agriculture and Livestock Sector in Tarhuna to describe the state of agricultural projects in the region, which cover a total area of about 79,956 hectares. The findings indicate that annual changes in production, productivity, and cultivated areas of wheat and barley are characterized by fluctuations due to the underutilization of agricultural land, which is linked to rainfall levels and climatic variability, in addition to weak planning and integration between public institutions and the private sector, as well as economic instability reflected in rising production costs. The results revealed that total wheat and barley production declined annually by 234.5686 and 260.2079 thousand quintals, respectively, with decreasing growth rates of 0.004226 and 0.021703, respectively. Although the cultivated area of wheat decreased during the study period at an annual rate of 0.045237, wheat productivity per hectare increased by 0.160206 quintals/ha, with an annual growth rate of 0.041726. As for barley, its cultivated area fluctuated slightly but ultimately increased by 0.621324, with a growth rate of 0.032128, while barley productivity per hectare showed a declining trend of 1.418971 quintals/ha. The study recommends enhancing the yield per hectare for both crops through implementing support policies for production inputs, raising farmers’ awareness of high-quality varieties, and activating the role of agricultural extension to promote the cultivation of improved and high-productivity varieties.